Measuring the Stability of University Rankings in the Field of Education (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The stability of ranking entities is one of the majorly discussed topics when concerning the ranking methodology. It is an important property which increases rankings reliability and credibility. Ranking of universities is, among others, an often examined topic in the terms of its stability, making the researchers worldwide agree that a statistically solid and firm ranking of universities is needed. This paper provides the stability analysis of the particular subject of the QS (Quacquarelli Symonds) World University Rankings compared to the University Ranking by Academic Performance (URAP). Namely, institutions that rank universities have turned the alertness from global academic rankings to more particular rankings in given scientific fields. In this paper, we particularly chose the field of Education, as one of the major factors that contribute to general well-being. We conducted the uncertainty and sensitivity analysis on the QS and URAP rankings in the field of Education to analyze the effects of their weighting schemes. The main goal of this paper is to compare the stability of QS and URAP ranking methodologies. Furthermore, we propose a Composite I-distance Indicator(CIDI) methodology as a tool for implementing the distinguishing innovations into the ranking methodology, in order to provide a more stable and solid ranking lists.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.